CAPTURING, ENCODING, EXPLAINING AND SHARING: A CASE STUDY IN A PUBLIC ORGANIZATION - Marques Junior, E.; Albino, J. P. [UNESP]; Marques, E. M. R. [UNESP]; Zambelo, E.; Vitoreli, M. C.; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education & Development, 2018)
The purpose of this paper is to present a case study of knowledge management emphasizing the capturing, encoding, sharing and dissemination of this knowledge, following the model proposed by Nonaka and Takeushi. Knowledge management is a subject that has gained increasing importance, especially by the need to capture the tacit knowledge - inside people's minds - and encode it, which allows its use by others, increasing its applicability. The study was carried out at the Bauru Undergraduate School of Engineering (FEB) that has experienced a significant shortage of staff, especially due to the retirement of some employees, as well as a significant increase of courses offered by the Undergraduate School. In order to solve this problem of expert loss and training of new employees, the Undergraduate School developed a procedures manual that is currently under presentation for professionals involved in the courses where they can make suggestions for improvements before the deployment stage. The methodological approach selected was the case study, and the deployment, as well as the facilities and difficulties found during this phase, will be object of study later.
Keywords: Knowledge Management; Process Management; Public Organizations